Tingkat Risiko Pendapatan dan Faktor yang Mempengaruhi Pendapatan Usahatani Tebu Keprasan - Saputro, Arief Joko; Rianti, Titis Surya Maha (Jurnal Sosial Ekonomi Pertanian, 2024)
This research aims to (1) analyze the factors that influence Keprasan sugar cane farming income as well as; (2) the level of risk of income and costs in Keprasan sugar cane farming. The data analysis method used is multiple linear regression with the Cobb-Douglass function model approach and coefficient of variation (CV) analysis. Factors significantly influencing Keprasan sugar cane farming income include production variables, P fertilizer, K fertilizer, and pesticides. The income risk faced by farmers is based on the CV calculation results, the CV value is 0.97, which means the opportunity for losses that sugar cane farmers must bear is 0.97 IDR/Ha. The CV value of 0.97 indicates the criteria are more than 0.5 and the L value is less than 0, which means that the risk of sugarcane farming income is categorized as a high-risk farming business.